RNAi silencing of wheat gliadins alters the network of transcription factors that regulate the synthesis of seed storage proteins toward maintaining grain protein levels - Marín-Sanz, Miriam; Barro, Francisco (Frontiers in Plant Science, 2022)
Gluten proteins are responsible for the unique viscoelastic properties of wheat dough, but they also trigger the immune response in celiac disease patients. RNA interference (RNAi) wheat lines with strongly silenced gliadins were obtained to reduce the immunogenic response of wheat. The E82 line presents the highest reduction of gluten, but other grain proteins increased, maintaining a total nitrogen content comparable to that of the wild type. To better understand the regulatory mechanisms in response to gliadin silencing, we carried out a transcriptomic analysis of grain and leaf tissues of the E82 line during grain filling. A network of candidate transcription factors (TFs) that regulates the synthesis of the seed storage proteins (SSPs), α-amylase/trypsin inhibitors, lipid transfer proteins, serpins, and starch in the grain was obtained. Moreover, there were a high number of differentially expressed genes in the leaf of E82, where processes such as nutrient availability and transport were enriched. The source-sink communication between leaf and grain showed that many down-regulated genes were related to protease activity, amino acid and sugar metabolism, and their transport. In the leaf, specific proline transporters and lysine-histidine transporters were down- and up-regulated, respectively. Overall, the silencing of gliadins in the RNAi line is compensated mainly with lysine-rich globulins, which are not related to the proposed candidate network of TFs, suggesting that these proteins are regulated independently of the other SSPs. Results reported here can explain the protein compensation mechanisms and contribute to decipher the complex TF network operating during grain filling.